The Application of Video Viewing Therapy for Sensory Perception Disorders and Auditory Hallucinations at Soerojo Mental Hospital in Magelang - Munandar, Mamat; Sari Purbaningsih, Endah; Fadila, Erida (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: One of the symptoms of schizophrenia is auditory hallucinations. Hallucinations are false perceptions that occur as a result of maladaptive neurobiological responses. Hallucinations can be treated using two techniques: pharmacological and non-pharmacological. Pharmacological techniques involve collaborating with a doctor to administer medication such as Haloperidol, Serenace, Lodomer, and Chlorpromazine. Non-pharmacological techniques in this study include video therapy. The objective is to determine the effectiveness of video therapy in treating sensory perception hallucinations at Magelang Mental Hospital. Method: This study uses a qualitative approach with a case study design. Result: The case study results showed that sensory perception disorders were resolved. Therefore, it can be concluded that nursing care, which includes assessment, diagnosis, intervention, implementation, and evaluation, combined with the application of video therapy, effectively reduces the level of hallucinations, frequency of hallucinations, and duration of hallucinations in schizophrenia patients. Conclusion: After implementing video therapy for 3 days, it was found that video therapy can be applied to schizophrenia patients with auditory hallucinations.